Atenciones clínicas y mortalidad en una uci de neonatología en un hospital referencial de la Amazonía Peruana, 2022 – 2023 - Piera Rioja, Marilyn Sthefanie (2024)
Introduction: Neonatal mortality is an issue of vital importance of a country. In Peru, in the year 2021 there was a neonatal mortality rate of 7.1%, in the same year in Loreto a rate between 8.78 and 10.14% was reported. Given this important data, it has been recorded that the neonatal intensive care units (NICU) are overflowing with neonates who require specific clinical care for their survival. Among the various clinical attentions of vital importance to restore the health of neonates are the most frequent ones such as nutritional support, respiratory support, antibiotic treatment and phototherapy. These also contribute to neonatal mortality. Objective: To investigate the association between clinical care and neonatal mortality in a neonatal ICU in a referral hospital in the Peruvian Amazon, 2022-2023. Methods: An analytical, observational study with a cross-sectional and retrospective design will be used. Population: included 240 medical records of neonates hospitalized in a NICU. Results: a mortality rate of 12.9% was obtained. Clinical care showed that, in the NICU, the most commonly used ventilatory support was binasal cannula (33.8%) and CPAP (32.5%). A significant association was found between mortality and respiratory support (p = <0.001). The most prescribed nutritional support was mixed feeding (36.3%) and breast milk (33.8%). A statistically significant association was found between mortality and nutritional support (p = 0.001). Phototherapy was used in 41.7%; however, no statistically significant association with mortality was found. The use of antibiotic therapy showed a high prevalence of its use in the NICU (71.3%), with the most frequent combination being ampicillin and amikacin (51.2%); a statistically significant association was found between mortality and the use of antibiotic therapy (p = 0.011). Conclusion: Neonates admitted to the NICU of a referral hospital mostly required the use of binasal cannula, mixed feeding, used phototherapy and antibiotic therapy. In addition, it is observed that the use of mechanical ventilator, parenteral feeding and antibiotic therapy may be related to neonatal mortality in the NICU.